1989
DOI: 10.1136/bmj.298.6670.363
|View full text |Cite
|
Sign up to set email alerts
|

Timolol: a non-sedative anxiolytic premedicant for day cases.

Abstract: Delays before discharge notes and typed summaries were received bv the two practices Weybridge practice (combined discharge notc and prescription Dover practice for drugs to be taken home) (separate discharge note)No of patients admitted to hospital 57 62

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…High-bias-risk trials Burn 41 Coleman 42 Jakobsen 46 Jakobsen 45 Liu 48 Liu 36 Mackenzie 49 Magnusson 37 Stone on the outcomes of cardiovascular mortality and heart failure (figures 2 and 3). A test for interaction showed significant effects of trial quality on all-cause mortality, cardiovascular mortality, and non-fatal myocardial infarction (figures 2 and 3).…”
Section: Weight (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…High-bias-risk trials Burn 41 Coleman 42 Jakobsen 46 Jakobsen 45 Liu 48 Liu 36 Mackenzie 49 Magnusson 37 Stone on the outcomes of cardiovascular mortality and heart failure (figures 2 and 3). A test for interaction showed significant effects of trial quality on all-cause mortality, cardiovascular mortality, and non-fatal myocardial infarction (figures 2 and 3).…”
Section: Weight (%)mentioning
confidence: 99%
“…Five trials enrolled high surgical-risk patients (emergency surgery, vascular surgery), 3,5,27,32,40 five enrolled intermediate-risk or high surgical-risk patients, 4,6,28,30,38 22 enrolled intermediate surgical-risk patients (intrathoracic, intraperitoneal, carotid endarterectomy, head and neck, orthopedic, or prostate surgery), [22][23][24][25][26]31,[33][34][35][36][37]39,[41][42][43][44][45][46][47][48][49][50] and one enrolled low surgical-risk patients. 29 A sensitivity analysis on the basis of surgical risk categories showed a 63% decreased risk of all-cause mortality and a 44% decreased risk of non-fatal myocardial infarction in trials with high surgical risk (tables 2 and 3); this finding was driven largely by the trial by Poldermans and colleagues.…”
Section: Weight (%)mentioning
confidence: 99%
“…During peripheral vascular surgery14 and after cardiac operations15 metoprolol has been reported to have a positive effect on the myocardial oxygen economy with reduced incidence of myocardial ischaemia. Furthermore, metoprolol and other ß blockers have a strong anxiolytic effect comparable with the benzodiazepines but without concurrent sedation 16 17 18 19 20. This may be another positive effect of metoprolol in gastrointestinal endoscopy, and it should therefore be included in future controlled trials with metoprolol.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded nine studies which reported only major cardiovascular complications within 30 days of surgery [1,2,[21][22][23][24][25][26][27] and a further nine studies which did not present data on perioperative myocardial ischaemia [28][29][30][31][32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%